Pengaruh Kepemimpinan, Motivasi, Disiplin, dan Upah terhadap Kinerja Karyawan Bank BNI Syariah Indonesia - Ade Onny Siagian; Tri Widyastuti; Bambang Karsono; Primadi Candra Susanto; Hillman Mushaddiq Suaidy; Zul Asman (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study is to discuss the progress of Islamic Banks developing rapidly. based on resources, market share, productivity, and others. This was followed by internal administration, such as office expansion and administration. On the other hand, considering the human assets of Islamic Banks is very important in realizing the vision and mission. As a result, they have to make employee execution measures on purpose. This study uses a quantitative approach with the independent variables being authority, work teaching, inspiration, and compensation. The dependent variable used in this research is representative execution. The results of the study show that administration, work teaching, inspiration, and compensation basically affect representative efforts. can be seen from the amount of t count of 45.804 > t table of 2.51 with a significance level (sig) of 0.000 <0.05. At the same time the basis of complete authority providing higher wages and remuneration encourages inspiration for workers, teaching them to expand the performance of workers. As a result, these factors can advance representative implementation to create a common path at Bank BNI Syariah Indonesia Surabaya Branch, East Java. The conclusion states that independent factors affect the performance of workers. Therefore, as a result, these models are very appropriate for advancing bank workers to achieve their goals.